Limbic autoimmune encephalitis with antibodies to glutamate decarboxylase (GAD) - L. U. Ulukhanova; M. M. Yaraliev; S. M. Attaeva (Детские инфекции (Москва))
Limbic encephalitis (LE) is a rare neurological syndrome, in most cases has a paraneoplastic nature, but recently there has been a large number of observations of idiopathic autoimmune LE associated with antibodies to neuronal membrane proteins. A clinical case of a disease in a 13-year-old patient with the detection of antibodies to glutamate decarboxylase (GAD) is described. The debut of the disease is marked by a decrease in memory for current events after the first convulsive attack during 2 months.